Dielectric composition, method of producing dielectric composition, and stacked ceramic electronic component
By designing the core-shell structure and molybdenum ore phase structure in the dielectric composition of multi-layer ceramic electronic components, excessive rare earth elements are absorbed, and the problems of microstructure instability and life reduction caused by excessive rare earth elements are solved, and the effect of stabilizing microstructure and long life is achieved.
Patent Information
- Application Number
- JP2023150239
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
In multi-layer ceramic electronic components, adding a small amount of rare earth elements can improve the high-temperature characteristics and life, but if too many rare earth elements, it will lead to grain growth of perovskites, resulting in instability of microstructure and reducing the life of the dielectric.
A dielectric composition containing the first, second and third grains is adopted, wherein the first grain has a core-shell structure, the second grain contains a perovskite compound oxide, and the third grain has a molybdenum ore phase structure. Through the design of this composition, rare earth elements can be effectively absorbed to avoid excessive grain growth.
In the case of excessive presence of rare earth elements, the microstructure of the dielectric composition is maintained to be stable, and its life span is extended, while excessive grain growth is avoided.
Smart Images

Figure 2025042987000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a dielectric composition, a method for producing the dielectric composition, and a multilayer ceramic electronic component. [Background technology]
[0002] Multilayer ceramic electronic components such as multilayer ceramic capacitors (MLCCs) are used in high-frequency communication systems such as mobile phones. For example, Patent Document 1 discloses a dielectric ceramic composition that contains a barium titanate-based main component and subcomponents and in which the relative intensity of the pyrochlore phase containing rare earth elements is controlled in a powder X-ray diffraction (XRD) analysis after sintering, a dielectric material, and a multilayer ceramic capacitor that contains the same.
[0003] Furthermore, Patent Document 2 discloses a piezoelectric ceramic having crystal grains and grain boundaries between the crystal grains, in which the crystal grains contain barium titanate with a perovskite structure and the grain boundaries contain a metal oxide in which the abundance ratio of titanium is higher than that of barium, and a piezoelectric element using the same. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-124779 A [Patent Document 2] JP 2012-131669 A Summary of the Invention [Problem to be solved by the invention]
[0005] In dielectric compositions used in multilayer ceramic electronic components, the addition of rare earth elements to barium titanate is expected to improve the high-temperature characteristics and thus the life of the dielectric. However, if the rare earth elements are contained in such an excess that the pyrochlore phase segregates, the grain growth of barium titanate is promoted, the microstructure becomes unstable, and the life of the dielectric is shortened.
[0006] An object of the present disclosure is to provide a dielectric composition that can obtain a stable microstructure and exhibit a long life even when it contains an excess amount of a rare earth element. [Means for solving the problem]
[0007] One aspect of the present disclosure provides a dielectric composition comprising: first crystal particles having a core portion having a perovskite structure represented by the general formula ABO3 and a shell portion covering the core portion and containing a rare earth element; second crystal particles containing a barium titanate-based composite oxide in which the elemental ratio of barium to titanium is 0.70 or less; and third crystal particles having a pyrochlore phase represented by the general formula R2Ti2O7, where R is a rare earth element. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a dielectric composition which can obtain a stable microstructure and exhibit a long life even if it contains an excessive amount of rare earth elements. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic diagram of a photograph of the dielectric composition according to the embodiment taken with a scanning electron microscope (SEM). [Diagram 2] FIG. 1 is a perspective view of a multilayer ceramic electronic component (multilayer ceramic capacitor). [Diagram 3] 3 is a cross-sectional view taken along line AA in FIG. 2.
[0010] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings.
[0011] <Dielectric Composition> Fig. 1 is a schematic diagram of a photograph of the dielectric composition according to the embodiment taken by a scanning electron microscope (SEM). As shown in Fig. 1, the dielectric composition 100 according to the embodiment has first crystal particles 10, second crystal particles 20, and third crystal particles 30. In this specification, a crystal particle refers to an isolated particle that does not include a crystal grain boundary therein and is not aggregated with other particles.
[0012] The dielectric composition 100 is composed of a plurality of crystal grains, some of which are first crystal grains 10, some of which are second crystal grains 20, and still other parts of which are third crystal grains 30. The boundaries between the crystal grains constitute grain boundaries 40, and the boundary between any three adjacent crystal grains on the SEM observation surface constitutes a triple junction 50. This triple junction 50 can be composed of any three crystal grains in the dielectric composition 100.
[0013] The first crystal particle 10 has a core portion 11 and a shell portion 12. The core portion 11 and the shell portion 12 have a core-shell structure CS in which the core portion 11 is covered with the shell portion 12.
[0014] The core portion 11 constitutes the central region of the core-shell structure CS. The core portion 11 has a perovskite structure represented by the general formula ABO3. The perovskite structure represented by ABO3 has a three-dimensional structure in which the A site is located at the vertex of a cube, the B site is located at the center of the cube, and O is located at the face center. For example, when ABO3 is barium titanate (BaTiO3), barium (Ba) is located at the A site, titanium (Ti) is located at the B site, and oxygen (O) is located at the O site.
[0015] The element contained in the A site of the perovskite structure is not particularly limited, but is preferably barium, and the element contained in the B site of the perovskite structure is not particularly limited, but is preferably at least one of titanium, zirconium (Zr), and hafnium (Hf).
[0016] The element ratio in the entire dielectric composition is preferably the element ratio of the element (barium) capable of forming a solid solution in the A site to the sum of the elements (zirconium and hafnium) capable of forming a solid solution in the B site in the perovskite structure represented by ABO3 (hereinafter referred to as the A / B ratio), which is 0.80 or more and 0.99 or less, more preferably 0.85 or more and 0.99 or less, and even more preferably 0.90 or more and 0.99 or less.
[0017] The donor element and the acceptor element may be included in the core portion 11 as well as the shell portion 12. The donor element is an element that provides an electron or accepts a hole. The acceptor element is an element that accepts an electron or provides a hole.
[0018] The manner in which the donor element is contained in the core region 11 is not particularly limited, but it is preferable that the donor element is solid-dissolved in the core region 11. The manner in which the acceptor element is contained in the core region 11 is not particularly limited, but it is preferable that the acceptor element is solid-dissolved in the core region 11. In addition, the core region 11 does not necessarily need to contain a donor element or an acceptor element.
[0019] Examples of donor elements include vanadium (V), molybdenum (Mo), niobium (Nb), tantalum (Ta), and tungsten (W). Only one type of these donor elements may be included, or two or more types may be included.
[0020] Examples of the acceptor element include manganese (Mn), magnesium (Mg), calcium (Ca), chromium (Cr), etc. Only one type of these acceptor elements may be contained, or two or more types may be contained.
[0021] The donor element reduces the oxide ion defect concentration in the core portion 11, and the acceptor element increases the insulation of the core portion, increasing the resistivity of the dielectric composition, thereby improving the reduction resistance of the dielectric composition and lengthening its life.
[0022] The shell portion 12 covers the core portion 11 and constitutes a relaxor. A relaxor is a material whose dielectric constant has a broad peak and whose dielectric constant is frequency dependent. The shell portion 12 is a region that has a higher concentration of additives, mainly rare earth elements, compared to the core portion 11, and has a perovskite structure with a different lattice constant from that of the core portion 11.
[0023] The shell portion 12 contains a rare earth element. The rare earth element can function as a donor element in the shell portion 12. The mode in which the rare earth element is contained in the shell portion 12 is not particularly limited, but it is preferable that the rare earth element is solid-dissolved in the shell portion 12.
[0024] The rare earth element is a Group 3 element of the periodic table, and is preferably at least one selected from gadolinium (Gd), yttrium (Y), dysprosium (Dy), terbium (Tb), holmium (Ho), erbium (Er), and europium (Eu).
[0025] The concentration of the rare earth element in the dielectric composition 100 is not particularly limited, but is preferably 1 at% to 4 at%, more preferably 1 at% to 3.5 at%, and further preferably 3.3 at% to 2.0 at%. The concentration of the rare earth element is the atomic ratio (at%) of the rare earth element to titanium in the dielectric composition 100.
[0026] The second crystal particles 20 include a barium titanate-based composite oxide. The barium titanate-based composite oxide may be, for example, BaTi2O5, BaTi4O9, or BaTiO 11 , BaTiO 13 , Ba4Ti 11 O 26 , Ba4Ti 12 O 27 , Ba4Ti 13 O 30 , Ba4Ti 14 O 27 , and Ba6Ti 17 O 40 These include, but are not limited to, the following:
[0027] The barium titanate-based composite oxide contained in the second crystal particles 20 has an element ratio of barium to titanium of 0.70 or less, preferably 0.16 or more and 0.70 or less, and more preferably 0.16 or more and 0.50 or less. That is, the barium titanate-based composite oxide contained in the second crystal particles 20 is a compound containing an excess of titanium based on barium titanate.
[0028] The method for measuring the element ratio of barium to titanium is arbitrary, and for example, the element ratio can be measured using a scanning electron microscope energy dispersive X-ray analyzer (SEM-EDX), an analytical scanning electron microscope (SEM-EDS), etc. By using SEM-EDX, the element ratio of barium to titanium can be measured with high accuracy.
[0029] The barium titanate-based composite oxide having an element ratio of barium to titanium of 0.70 or less is not particularly limited, but is preferably BaTi2O5, BaTi4O9, BaTiO 11 , BaTiO 13 , Ba4Ti 11 O 26 , Ba4Ti 12 O 27 , Ba4Ti 13 O 30 , Ba4Ti 14 O 27 , and Ba6Ti 17 O 40 At least one selected from the above.
[0030] The barium titanate-based composite oxide is measured for its diffraction line profile by XRD. It can be identified by focusing on peaks other than the diffraction line intensity derived from the perovskite structure and referring to the PDF (Powder Diffraction File) issued by ICDD (International Centre for Diffraction Data; Pennsylvania, USA). 11 O 26In the present invention, the production can be evaluated by identifying the compound by reference to PDF-01-083-1459.
[0031] The third crystal particle 30 has a pyrochlore phase represented by the general formula R2Ti2O7. In the general formula, R represents a rare earth element. For example, referring to PDF-01-083-1459, the pyrochlore phase represented by Dy2Ti2O7 where R=Dy has a cubic crystal system, space group Fd-3m (No. 227), lattice constant a=10.1060 Å, and number of molecules in a unit cell Z=4.
[0032] In the general formula, R is an element of Group 3 of the periodic table excluding actinide elements, and is preferably at least one selected from gadolinium, yttrium, dysprosium, terbium, holmium, erbium, and europium. Note that R in R2Ti2O7 may be the same as or different from the rare earth element contained in the shell portion.
[0033] The pyrochlore phase represented by R2Ti2O7 indicates that the rare earth elements have reached the solubility limit in the core-shell structure and are fully dissolved.
[0034] The locations where the third crystal particles 30 of the pyrochlore phase represented by R2Ti2O7 exist are locations where excess rare earth oxides (R2O3) were present, but it is believed that the titania (TiO2) of the second crystal particles has diffused into some of the rare earth oxides and been replaced by the pyrochlore phase (R2Ti2O7). In other words, the pyrochlore segregation (R2Ti2O7) corresponds to the locations where excess rare earth oxides have been absorbed into segregations that contain excess titanium based on barium titanate.
[0035] In the dielectric composition 100, the third crystal particles 30 are adjacent to the first crystal particles 10, and some of the third crystal particles 30 are adjacent to the second crystal particles 20. In this specification, "adjacent" means that two crystal particles are formed in a position adjacent to each other across a grain boundary in the dielectric composition.
[0036] The locations where some of the third crystal particles 30 are adjacent to the second crystal particles 20 are considered to be locations where excess rare earth oxides were present and where titania from the second crystal particles 20 interdiffused to generate a pyrochlore phase (R2Ti2O7). In other words, the locations where the third crystal particles, which are pyrochlore phases, are adjacent to the second crystal particles, which are segregations containing an excess of titanium based on barium titanate, correspond to locations where excessive grain growth was suppressed due to the presence of the segregations containing an excess of titanium based on barium titanate, even though there were excess rare earth oxides present that caused slight pyrochlore segregation to be generated.
[0037] The average particle size of the first crystal particles 10, the second crystal particles 20 and the third crystal particles 30 is not particularly limited, but is preferably 100 nm or more and 320 nm or less, more preferably 110 nm or more and 310 nm or less, and even more preferably 120 nm or more and 300 nm or less.
[0038] Here, the average particle size of the crystal particles is determined by observing the dielectric composition with a scanning electron microscope (SEM), drawing multiple parallel lines in the photograph, and cutting each line at the periphery of each crystal particle in the dielectric composition. The length of the line segment, i.e., the distance between the two points where each line intersects with the periphery of each crystal particle, is taken as the particle size of each crystal particle. The particle size of each crystal particle is measured for 400 or more crystal particles, and the average of the results is taken as the average particle size.
[0039] As described above, the dielectric composition of the present disclosure has the second crystal particles 20 including segregations containing an excess of titanium based on barium titanate and the third crystal particles 30 including a pyrochlore phase, and thus there are portions in the dielectric composition where excess rare earth oxides are absorbed by the segregations containing an excess of titanium based on barium titanate. This suppresses excessive grain growth of the core-shell structure, and the first crystal particles 10 having a stable core-shell structure in which the rare earth element is dissolved are obtained. Therefore, even if the dielectric composition of the present disclosure contains an excess of rare earth elements, a stable microstructure can be obtained, and the dielectric can have a long life.
[0040] In addition, as described above, since barium is contained in the A site of the perovskite structure and at least one of titanium, zirconium, and hafnium is contained in the B site, even when ZrO2 or HfO2 is added, the titanium element of barium titanate is substituted with zirconium or hafnium to form a solid solution during the sintering process, and the titanium element that has escaped from the perovskite structure reacts with other barium titanate to form segregations that contain an excess of titanium based on barium titanate.
[0041] In this way, by dissolving the zirconium element or the hafnium element in the titanium element of the barium titanate, a liquid phase component containing an excess of titanium based on the barium titanate is formed in the dielectric composition, and the grain boundaries of the crystal grains with the core-shell structure are covered, thereby suppressing excessive grain growth. This makes it possible to highly refine the grain size of the dielectric composition and further improve the life of the dielectric.
[0042] Furthermore, as described above, by making the element ratio of barium to the sum of titanium, zirconium and hafnium (A / B ratio) 0.80 or more and 0.99 or less, excessive grain growth is reliably suppressed while maintaining the dielectric properties, and the life of the dielectric can be further improved.
[0043] Furthermore, as described above, when the rare earth element is at least one selected from gadolinium, yttrium, dysprosium, terbium, holmium, erbium, and europium, the rare earth element is likely to substitute for and form a solid solution at both the A site and the B site of the perovskite structure, thereby making it possible to extend the life of the dielectric.
[0044] Furthermore, as described above, when the rare earth element concentration is 1 at% or more and 4 at% or less, the rare earth element is contained in such an excessive amount that pyrochlore segregation occurs, but since there is segregation containing an excess of titanium based on barium titanate, excessive grain growth does not occur, and a core-shell structure in which sufficient rare earth elements are dissolved is obtained. This makes it possible to refine the crystal grains of the dielectric composition and reliably extend the life of the dielectric.
[0045] Furthermore, as described above, when the average particle size of the first crystal particles, the second crystal particles and the third crystal particles is 100 nm or more and 320 nm or less, a dielectric composition having a stable microstructure can be obtained, in which the rare earth element is sufficiently dissolved in the first crystal particles to form a core-shell structure.
[0046] As described above, the barium titanate-based composite oxides are BaTi2O5, BaTi4O9, and BaTiO 11 , BaTiO 13 , Ba4Ti 11 O 26 , Ba4Ti 12 O 27 , Ba4Ti 13 O 30 , Ba4Ti 14 O 27 , and Ba6Ti 17 O 40 When at least one of the above is selected, the barium titanate-based composite oxide contained in the second crystal particles is reliably produced as a segregation containing an excess of titanium based on barium titanate, which prevents the first crystal particles from undergoing excessive grain growth, maintains stable dielectric properties, and enables the dielectric to have a longer life.
[0047] In addition, as described above, since some of the third crystal grains are adjacent to the second crystal grains, the excess rare earth oxide and the segregation containing excess titanium based on barium titanate interdiffuse to such an extent that a slight pyrochlore phase is generated, resulting in a stable core-shell structure in which sufficient rare earth elements are dissolved in solid solution. This allows the crystal grains of the dielectric composition to be highly refined, and further enables the dielectric to have a long life.
[0048] <Method of Manufacturing Dielectric Composition> The method for producing a dielectric composition according to the present disclosure is a method for producing the dielectric composition of the above-described embodiment.
[0049] That is, the dielectric composition obtained by the manufacturing method of the present disclosure is a dielectric composition 100 having a first crystal particle 10 having a core portion 11 having a perovskite structure represented by the general formula ABO3 and a shell portion 12 covering the core portion 11 and containing a rare earth element, a second crystal particle 20 containing a barium titanate-based composite oxide in which the elemental ratio of barium to titanium is 0.70 or less, and a third crystal particle 30 having a pyrochlore phase represented by the general formula R2Ti2O7 (wherein R is a rare earth element) (see FIG. 1).
[0050] The method for producing the dielectric composition of the present disclosure includes a step of firing the dielectric composition (firing step). In this firing step, the heating rate is preferably 3000°C / h or more and 10000°C / h or less, more preferably 4000°C / h or more and 9000°C / h or less, and even more preferably 5000°C / h or more and 8000°C / h or less.
[0051] In the firing step, the firing temperature is arbitrary, but is preferably 900°C or higher and 1500°C or lower, more preferably 1000°C or higher and 1400°C or lower, and further preferably 1100°C or higher and 1300°C or lower.
[0052] In the manufacturing method of the dielectric composition of the present disclosure, the heating rate in the firing step is 3000°C / h or more and 10000°C / h or less, thereby preventing the aggregation of liquid phase components that contain an excess of titanium based on barium titanate.
[0053] This allows the grain growth to be suppressed by retaining the segregation containing an excess of titanium based on barium titanate in the dielectric composition at the grain boundary, and also allows it to be dispersed or dispersed in small amounts in the dielectric composition. As a result, even if an excessive amount of rare earth element is added so that a pyrochlore phase is slightly generated, the segregation containing an excess of titanium based on barium titanate that is dispersed in small amounts in the dielectric composition becomes a core-shell structure in which the rare earth element is sufficiently dissolved in barium titanate, and the dielectric composition has a stable microstructure, thereby enabling the dielectric composition to have a long life.
[0054] In Patent Document 2, barium titanate-based piezoelectric ceramics containing segregation that contains an excess of titanium based on barium titanate are fired at a heating rate of 10°C / min, but when a dielectric composition is fired at a heating rate of 10°C / min according to this Patent Document, the average grain size of the dielectric composition becomes 2 μm or more. In a multilayer ceramic electronic component using a dielectric composition with an average grain size of 2 μm or more, the number of grain boundaries is reduced, which may significantly deteriorate the life and insulation properties.
[0055] In contrast, in the manufacturing method of the dielectric composition disclosed herein, the average particle size of the first crystal particles, the second crystal particles and the third crystal particles can be controlled to 100 nm or more and 320 nm or less by firing the dielectric composition containing the second crystal particles, which includes a barium titanate-based composite oxide in which the element ratio of barium to titanium is 0.70 or less, at a temperature increase rate of 3000°C / h or more and 10000°C / h or less.
[0056] In the method for producing a dielectric composition according to the present disclosure, it is believed that the aggregation of liquid phase components containing an excess of titanium based on barium titanate is prevented by increasing the heating rate, and grain growth is suppressed by retaining them in the grain boundaries. As a result, according to the method for producing a dielectric composition according to the present disclosure, even if the rare earth element is excessively contained so that a pyrochlore phase is slightly generated, a stable core-shell structure in which the rare earth element is sufficiently dissolved can be obtained, and the life of the dielectric can be extended.
[0057] <Multilayer ceramic electronic components> The multilayer ceramic electronic component according to the embodiment of the present disclosure uses the dielectric composition of the above-mentioned embodiment. That is, the multilayer ceramic electronic component according to the present embodiment can use the dielectric composition 100 having the above-mentioned first crystal grains 10, second crystal grains 20, and third crystal grains 30.
[0058] Examples of the multilayer ceramic electronic components include multilayer ceramic capacitors, chip varistors, chip thermistors, multilayer inductors, and piezoelectric elements.
[0059] Fig. 2 is a perspective view of a multilayer ceramic capacitor, which is an example of the multilayer ceramic electronic component of this embodiment, and Fig. 3 is a cross-sectional view taken along line AA in Fig. 2. In each figure, a three-dimensional orthogonal coordinate system with three axial directions is used, with the longitudinal direction of the multilayer ceramic capacitor defined as the X direction, the width direction defined as the Y direction, and the height direction defined as the Z direction.
[0060] 2 and 3, the multilayer ceramic capacitor 200 includes a laminated chip 60 having a substantially rectangular parallelepiped shape, and external electrodes 70, 80 provided on two opposing end faces of the laminated chip 60. Of the four faces of the laminated chip 60 other than the two end faces, the two faces other than the top and bottom faces in the stacking direction are referred to as side faces. The external electrodes 70, 80 extend on the top, bottom and two side faces in the stacking direction of the laminated chip 60, and are spaced apart from each other in the X direction.
[0061] The laminated chip 60 has a configuration in which internal electrode layers 90 containing a base metal material and dielectric layers 101 containing the dielectric composition 100 of the above-mentioned embodiment are alternately laminated. The edges of the internal electrode layers 90 are alternately connected to the end faces of the laminated chip 60 on which the external electrodes 70 are provided and the end faces on which the external electrodes 80 are provided. As a result, the internal electrode layers 90 are alternately electrically connected to the external electrodes 70 and the external electrodes 80.
[0062] As a result, the multilayer ceramic capacitor 200 has a configuration in which a plurality of dielectric layers 101 are laminated with the internal electrode layers 90 interposed therebetween. In addition, in a laminate L of the dielectric layers 101 and the internal electrode layers 90, the internal electrode layers 90 are disposed on the outermost layers in the Z direction, and the upper and lower surfaces of the laminate L are covered with cover layers C. The cover layers C are mainly composed of a ceramic material. In this embodiment, the cover layers C are composed of the same dielectric composition 100 as the dielectric layers 101.
[0063] The size of the multilayer ceramic capacitor 200 is, for example, 0.25 mm in length, 0.125 mm in width, and 0.125 mm in height, or 0.4 mm in length, 0.2 mm in width, and 0.2 mm in height, or 0.6 mm in length, 0.3 mm in width, and 0.3 mm in height, or 1.0 mm in length, 0.5 mm in width, and 0.5 mm in height, or 3.2 mm in length, 1.6 mm in width, and 1.6 mm in height, or 4.5 mm in length, 3.2 mm in width, and 2.5 mm in height, but is not limited to these sizes.
[0064] The internal electrode layers 90 are mainly composed of base metals such as nickel (Ni), copper (Cu), tin (Sn), etc. The internal electrode layers 90 may be made of precious metals such as platinum (Pt), palladium (Pd), silver (Ag), gold (Au), etc., or alloys containing these metals.
[0065] 3, a region where an internal electrode layer 90 connected to an external electrode 70 and an internal electrode layer 90 connected to an external electrode 80 face each other is a capacitive region that generates capacitance in the multilayer ceramic capacitor 200. The capacitive region is a region where adjacent internal electrode layers 90 connected to different external electrodes face each other in the Z direction.
[0066] The regions where the internal electrode layer 90 connected to the external electrode 70 faces the external electrode 80 without passing through the internal electrode layer 90 connected to the external electrode 80 (end margin), and the regions where the internal electrode layer 90 connected to the external electrode 80 faces the internal electrode layer 90 connected to the external electrode 70 without passing through (end margin) are regions that do not generate capacitance. Also, the regions from both side surfaces of the multilayer chip 60 to the internal electrode layer 90 (side margin) are regions provided to cover the ends where the plurality of internal electrode layers 90 laminated in the above laminate L extend to the side surfaces, and this side margin is also a region that does not generate capacitance.
[0067] In the multilayer ceramic capacitor 200 according to the present embodiment, the dielectric composition 100 that constitutes the dielectric layer 101 is included in the capacitance region. Thereby, the effects of the dielectric composition of the present embodiment described above can be obtained.
[0068] That is, in the multilayer ceramic electronic component of the present embodiment, by using a dielectric composition having second crystal particles containing segregation with excessive titanium based on barium titanate and third crystal particles containing a pyrochlore phase, first crystal particles having a stable core-shell structure in which rare earth elements are solid-solved can be obtained. Therefore, the multilayer ceramic electronic component of the present disclosure can improve the life of the dielectric without degrading the dielectric characteristics even if the dielectric composition contains an excessive amount of rare earth elements.
Example
[0069] Hereinafter, the present embodiment will be further described using experimental examples. Also, various tests and evaluations follow the following methods.
[0070] <Fabrication of MLCC (sample)> Barium titanate with an average particle size of 100 nm was weighed, and various additives and organic solvents were mixed to a predetermined ratio. Here, TiO2 was added as an additive, so that the element ratio of the element contained in the A site, i.e., barium, to the total of the elements contained in the B site, i.e., titanium, zirconium, and hafnium, in the perovskite structure was 0.900 to 0.990. The prepared dielectric raw material powder was wet mixed with an organic solvent. The slurry obtained by adding a binder was applied to a 2.5 μm thick dielectric green sheet by the doctor blade method and dried. A conductive paste film containing Ni was screen printed on the green sheet in a predetermined pattern. In addition, in order to fill the step between the green sheet and the conductive paste film, a reverse pattern sheet having a pattern complementary to the conductive paste film was screen printed on the green sheet. Ten layers were stacked, pressed, and cut. As a result, an MLCC molded body with dimensions of 1.0 mm in length, 0.5 mm in width, and 0.5 mm in height was obtained.
[0071] The MLCC molded sample was debindered at 300°C in a nitrogen (N2) atmosphere. It was then sintered at a temperature range of 1150°C to 1250°C. The heating rate was 6000°C / h. The oxygen partial pressure was 10 -5 ~10 -8 The MLCC samples were sintered in a reducing atmosphere at 1000 MPa (atm). After cooling, the samples were heated to a temperature range of 800°C to 1050°C in a nitrogen atmosphere, and the temperature was maintained for reoxidation. To form external electrodes on the sintered MLCC samples, nickel paste containing glass frit was applied to both end faces where the internal electrodes were exposed, and baked in a nitrogen atmosphere. Thus, MLCC samples were obtained. The average layer thickness of the dielectric composition after sintering was approximately 2.0 μm, and the average intersection area was 0.268 mm.
[0072] <Particle size (average particle size) of barium titanate particles> The particle size of the barium titanate particles was measured by the following procedure. First, a dielectric composition containing barium titanate particles (specifically, an element using the dielectric composition) was cut or polished to expose an observation surface. The exposed observation surface was processed to be smooth enough to be judged as a mirror surface using diamond paste or the like of 2 μm or less. Next, a conductive material such as platinum or osmium was vapor-deposited on the smooth observation surface, and then the surface was observed with a scanning electron microscope (SEM) and photographed to obtain a photograph of the barium titanate particles. Next, multiple parallel straight lines were drawn in the photograph, and the length of each line segment cut at the periphery of each barium titanate particle, that is, the distance between two points where each straight line intersects with the periphery of the barium titanate particle, was taken as the particle size of the barium titanate particles. Using this method, the particle size of the barium titanate particles was measured for 400 or more particles, and the average of the results was taken as the average particle size of the barium titanate particles.
[0073] If the outline of the barium titanate particles is difficult to see on the exposed observation surface, the exposed observation surface is subjected to a heat treatment (thermal etching) for about 5 minutes at a temperature about 50°C lower than the baking temperature prior to deposition of platinum or osmium, etc. Alternatively, instead of this heat treatment, the observation surface may be chemically etched using an acid such as hydrofluoric acid, hydrochloric acid, sulfuric acid, nitric acid, or a mixture of two or more of these acids at a concentration appropriate for etching.
[0074] It was determined that when the average grain size was less than 350 nm, the microstructure of the crystal grains was stable, whereas when the average grain size was 350 nm or more, the microstructure of the crystal grains was unstable.
[0075] <Presence or absence of pyrochlore phase and segregation containing excess titanium based on barium titanate> A sample for observation with a transmission electron microscope (TEM) was cut out from the dielectric composition using a focused ion beam (FIB) device, etc. The cut out sample was observed with a TEM equipped with an energy dispersive X-ray spectroscopy (EDS) or a wavelength dispersive X-ray spectroscopy (WDS) to determine the crystal grains to be measured.
[0076] Note that by observing with a SEM instead of a TEM, the pyrochlore phase tends to be observed brightly in the backscattered electron image, and segregations containing an excess of titanium based on barium titanate tend to be observed darkly, so the crystal grains can be estimated from the contrast of the backscattered electron image. However, since yttrium has a small atomic number, it is not possible to estimate the crystal grains from the contrast of the backscattered electron image.
[0077] Alternatively, the area ratio of segregated particles to dielectric particles may be obtained by binarizing the image using image processing software. 2 When the area ratio of the pyrochlore phase to the dielectric composition excluding the internal electrodes in the above-mentioned regions was determined, it was 1% or less in all of the examples.
[0078] Furthermore, XRD can also be used to confirm the pyrochlore phase and segregation containing an excess of titanium relative to barium titanate. Note that while the pyrochlore phase can be detected by powder XRD, segregation containing an excess of titanium relative to barium titanate has a complex crystal structure, so it can be difficult to determine the presence or absence of segregated particles using XRD alone. For this reason, it is preferable to combine the above-mentioned evaluation of the microstructure with powder XRD evaluation to determine the presence or absence of segregated particles.
[0079] <halt> In the Highly Accelerated Limit Test (HALT), the temperature was 138°C, and a voltage of 50V was applied to a layer thickness of 1μm of the dielectric composition to evaluate. The time when the leakage current value exceeded 1mA from the start of the test was determined to be the time to failure, and the average life value was calculated. The average life value was determined as ◯ (good) for 1000min or more, and × (bad) for less than 1000min.
[0080] Examples and comparative examples are listed below, and the evaluation results are shown in Table 1.
[0081] [Example 1] A sample was prepared with an A / B ratio (Ba / Ti+Zr+Hf) of 0.990 and 2.0% dysprosium added as a rare earth element to titanium. The average grain size, the presence or absence of segregation containing excess titanium based on barium titanate, the presence or absence of pyrochlore phase, and the average HALT life value were evaluated.
[0082] [Example 2] A sample was prepared and evaluated in the same manner as in Example 1, except that the A / B ratio was set to 0.980.
[0083] [Example 3] A sample was prepared and evaluated in the same manner as in Example 1, except that the A / B ratio was set to 0.960 and dysprosium was added at 1.0% relative to titanium.
[0084] [Example 4] Furthermore, dysprosium was added in an amount of 2.0% relative to titanium, and otherwise samples were prepared in the same manner as in Example 3 and evaluated.
[0085] [Example 5] Furthermore, dysprosium was added in an amount of 3.0% relative to titanium, and otherwise samples were prepared in the same manner as in Example 3 and evaluated.
[0086] [Example 6] Furthermore, instead of dysprosium, erbium was added in an amount of 2.0% relative to titanium, and otherwise samples were prepared and evaluated in the same manner as in Example 4.
[0087] [Example 7] Furthermore, instead of dysprosium, yttrium was added in an amount of 2.0% relative to titanium, and otherwise samples were prepared and evaluated in the same manner as in Example 4.
[0088] [Example 8] Furthermore, instead of dysprosium, holmium was added in an amount of 2.0% relative to titanium, and otherwise samples were prepared and evaluated in the same manner as in Example 4.
[0089] [Example 9] Furthermore, instead of dysprosium, terbium was added in an amount of 2.0% relative to titanium, and other than that, samples were prepared and evaluated in the same manner as in Example 4.
[0090] [Example 10] Furthermore, instead of dysprosium, gadolinium was added in an amount of 2.0% relative to titanium, and other than that, samples were prepared and evaluated in the same manner as in Example 4.
[0091] [Example 11] Furthermore, instead of dysprosium, europium was added in an amount of 2.0% relative to titanium, and otherwise samples were prepared and evaluated in the same manner as in Example 4.
[0092] [Example 12] A sample was prepared and evaluated in the same manner as in Example 1, except that the A / B ratio was set to 0.940.
[0093] [Example 13] A sample was prepared and evaluated in the same manner as in Example 1, except that the A / B ratio was set to 0.900.
[0094] [Comparative Example 1] A sample was prepared and evaluated in the same manner as in Example 5, except that the A / B ratio was set to 0.995.
[0095] [Comparative Example 2] A sample was prepared and evaluated in the same manner as in Example 3, except that dysprosium was added in an amount of 0.8% relative to titanium.
[0096] [Comparative Example 3] A sample was prepared and evaluated in the same manner as in Example 1, except that the A / B ratio was set to 1.010.
[0097] [Table 1]
[0098] From Table 1, in Examples 1 to 13, the samples with an A / B ratio of 0.900 to 0.990 and containing 1.0 to 3.0% rare earth element had an average particle size of 140 to 290 nm, and both segregation containing excess titanium based on barium titanate and pyrochlore phase were detected, and the average life value was good. From these results, it was found that barium titanate particles in which segregation containing excess titanium based on barium titanate and pyrochlore phase were generated had a stable microstructure and a long life.
[0099] In addition, in Examples 4 and 6 to 11, when comparing the types of rare earth elements, the average life value exceeded 4000 min for dysprosium, terbium, and gadolinium. From this result, it is considered that, among the rare earth elements, dysprosium, terbium, and gadolinium are easily dissolved in barium titanate, and contribute to a longer life.
[0100] On the other hand, according to Comparative Example 1, the sample with an A / B ratio of 0.995 had an average particle size of 452 nm, no segregation containing excessive titanium based on barium titanate was detected, and the average life value was 0 minutes. From this result, it was found that barium titanate particles in which no segregation containing excessive titanium based on barium titanate is generated have an unstable microstructure and cannot express a life.
[0101] In addition, according to Comparative Example 2, the sample containing 0.8% rare earth element (Dy) had an average particle size of 213 nm, no pyrochlore phase was detected, and an average lifespan of 720 minutes. This result shows that barium titanate particles containing an insufficient amount of rare earth element to produce a pyrochlore phase cannot exhibit a long lifespan.
[0102] Furthermore, according to Comparative Example 3, the sample with an A / B ratio exceeding 1 had an average particle size of 354 nm, and neither segregation containing an excess of titanium based on barium titanate nor pyrochlore phase was detected. This result shows that barium titanate particles in which neither segregation containing an excess of titanium based on barium titanate nor pyrochlore phase is generated do not undergo grain growth inhibition, leading to an unstable microstructure and failure to achieve a long life.
[0103] Preferred aspects of the present disclosure will be described below.
[0104] (Appendix 1) A first crystal particle having a core portion having a perovskite structure represented by a general formula ABO3 and a shell portion covering the core portion and containing a rare earth element; second crystal particles including a barium titanate-based composite oxide having an elemental ratio of barium to titanium of 0.70 or less; and third crystal particles having a pyrochlore phase represented by the general formula R2Ti2O7, where R is the rare earth element.
[0105] (Appendix 2) the element contained in the A site of the perovskite structure is barium; The dielectric composition according to claim 1, wherein the element contained in the B site of the perovskite structure is at least one of titanium, zirconium, and hafnium.
[0106] (Appendix 3) The dielectric composition according to claim 2, wherein an elemental ratio of the barium to the sum of the titanium, the zirconium, and the hafnium is 0.80 or more and 0.99 or less.
[0107] (Appendix 4) 4. The dielectric composition according to claim 1, wherein the rare earth element is at least one selected from gadolinium, yttrium, dysprosium, terbium, holmium, erbium, and europium.
[0108] (Appendix 5) 5. The dielectric composition according to claim 1, wherein the concentration of the rare earth element is 1 at % or more and 4 at % or less.
[0109] (Appendix 6) 6. The dielectric composition according to claim 1, wherein the first crystal particles, the second crystal particles, and the third crystal particles have an average particle size of 100 nm or more and 320 nm or less.
[0110] (Appendix 7) The barium titanate-based composite oxide is BaTi2O5, BaTi4O9, BaTi5O 11 , BaTiO 13 , Ba4Ti 11 O 26 , Ba4Ti 12 O 27 , Ba4Ti 13 O 30 , Ba4Ti 14 O 27 , and Ba6Ti 17 O 40 7. The dielectric composition according to any one of claims 1 to 6, wherein the dielectric composition is at least one selected from the following:
[0111] (Appendix 8) some of the third crystal particles are adjacent to the second crystal particles; 8. A dielectric composition according to any one of claims 1 to 7.
[0112] (Appendix 9) A method for producing a dielectric composition according to any one of claims 1 to 8, comprising the steps of: A method for producing a dielectric composition, comprising a step of firing the dielectric composition at a temperature rise rate of 3000° C. / h or more and 10000° C. / h or less.
[0113] (Appendix 10) A multilayer ceramic electronic component using the dielectric composition according to any one of claims 1 to 8.
[0114] Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the specific embodiments, and various modifications and changes are possible within the scope of the invention described in the claims. [Explanation of symbols]
[0115] 100 Dielectric composition 101 Dielectric layer 10 First crystal particle 11 Core 12 Shell part CS core-shell structure 20 Second crystal particle 30 Third crystal particle 40 grain boundaries 50 Triple Point 200 Multilayer ceramic capacitors 60 Stacked Chips 70 External electrode 80 External electrode 90 Internal electrode layer C. Cover layer L laminate< / halt>
Claims
1. General formula ABO 3 A first crystal particle having a core portion having a perovskite structure represented by the formula (I) and a shell portion covering the core portion and containing a rare earth element; second crystal particles including a barium titanate-based composite oxide having an elemental ratio of barium to titanium of 0.70 or less; R is the rare earth element represented by the general formula R 2 Ti 2 O 7 and third crystal particles having a pyrochlore phase represented by the formula:
2. the element contained in the A site of the perovskite structure is barium; 2. The dielectric composition according to claim 1, wherein an element contained in the B site of the perovskite structure is at least one of titanium, zirconium, and hafnium.
3. 3. The dielectric composition according to claim 2, wherein an element ratio of said barium to the sum of said titanium, said zirconium and said hafnium is 0.80 or more and 0.99 or less.
4. 2. The dielectric composition of claim 1, wherein the rare earth element is at least one selected from gadolinium, yttrium, dysprosium, terbium, holmium, erbium and europium.
5. 2. The dielectric composition according to claim 1, wherein the concentration of the rare earth element is 1 at % or more and 4 at % or less.
6. 2. The dielectric composition according to claim 1, wherein the first crystal particles, the second crystal particles and the third crystal particles have an average particle size of 100 nm or more and 320 nm or less.
7. The barium titanate-based composite oxide is BaTi 2 O 5 ,BaTi 4 O 9 ,BaTi 5 O 11 ,BaTi 6 O 13 , Ba 4 Ti 11 O 26 , Ba 4 Ti 12 O 27 , Ba 4 Ti 13 O 30 , Ba 4 Ti 14 O 27 , and Ba 6 Ti 17 O 40 The dielectric composition according to claim 1 , which is at least one selected from the following:
8. some of the third crystal grains are adjacent to the second crystal grains; The dielectric composition of claim 1 .
9. A method for producing the dielectric composition according to any one of claims 1 to 8, comprising the steps of: A method for producing a dielectric composition, comprising a step of firing the dielectric composition at a temperature rise rate of 3000° C. / h or more and 10000° C. / h or less.
10. A multilayer ceramic electronic part using the dielectric composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Piezoelectric ceramics, manufacturing method therefor, piezoelectric element, liquid discharge head, ultrasonic motor, and dust removal device
JP2012131669A
Dielectric ceramic composition, dielectric material and multilayer ceramic capacitor including the same
JP2016124779A